2006
DOI: 10.1021/ac060551t
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanofiber-Based Glucose Biosensor

Abstract: The use of highly activated carbon nanofibers for the design of catalytic electrochemical biosensors is demonstrated. The direct immobilization of enzymes onto the surface of carbon nanofibers is shown to be a highly efficient method for the development of a new class of very sensitive, stable, and reproducible electrochemical biosensors. These results establish the fact that the carbon nanofiber is the best matrix so far described for the development of biosensors, far superior to carbon nanotubes or graphite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
191
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(195 citation statements)
references
References 38 publications
4
191
0
Order By: Relevance
“…Vamvakaki reported a glucose biosensor based on highly-activated CNFs with direct enzyme immobilization [56]. This is a highly efficient method for developing very sensitive, stable, reproducible electrochemical biosensors.…”
Section: Biosensors Based On Carbon Nanofibersmentioning
confidence: 99%
“…Vamvakaki reported a glucose biosensor based on highly-activated CNFs with direct enzyme immobilization [56]. This is a highly efficient method for developing very sensitive, stable, reproducible electrochemical biosensors.…”
Section: Biosensors Based On Carbon Nanofibersmentioning
confidence: 99%
“…Extensive work has been carried out with redox protein films over the past few decades in order to find methods to increase the electron transfer rate between enzyme and electrode [1 8]. For example, a variety of carbonbased materials such as carbon nanotubes (CNTs) [9 11] and carbon nanofi bers (CNFs) [12,13] have been successfully employed for the direct electron transfer of proteins in fi lms. Their properties of hydrophilicity, nontoxicity, excellent film-forming ability, and remarkable biocompatibility offer excellent prospects for biocompatible immobilization matrices and the design of novel biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…VACNFs were also used for biosensing applications (Baker et al, 2006 b). The use of highly activated CNFs for the preparation of glucose biosensors, in comparison with SWCNT and graphite powder, is presented by Vamvakaki et al, 2006. They demonstrated that CNFs are far superior to carbon nanotubes or graphite powder as matrix for the immobilization of proteins and enzymes and for the development of biosensors.…”
Section: Carbon Nanofibers As Sensorsmentioning
confidence: 99%